Modelling microstructural changes of ordinary Portland cement paste at elevated temperature. Issue 1 (28th September 2018) - Zhang, Qi; Ye, Guang
Abstract : On the material level, the deterioration of ordinary Portland cement (OPC) paste at elevated temperature is attributed to chemical transitions and microstructural cracking. However, few studies on the quantitative characterisation of the degradation process of OPC paste have been reported and thus the quantitative relationship between microcracking and strength loss of OPC paste remains unclear. A simulation procedure for modelling the microstructural changes of OPC paste at elevated temperature was developed in this work. After the microstructural simulation, a virtual tensile test was performed on fire-damaged microstructures in order to evaluate the tensile strength and Young's modulus. The strength losses of OPC paste due to both chemical transitions and microcracking were then quantified.